PARAMETERS OF KAMCHATKA SEISMICITY IN 2008 - Vadim A. Saltykov; Nadezhda M. Kravchenko (Геодинамика и тектонофизика, 2015)
The paper describes seismicity of Kamchatka for the period of 2008 and presents 2D distribution of background seismicity parameters calculated from data published in the Regional Catalogue of Kamchatka Earthquakes. Parameters under study are total released seismic energy, seismic activity A10, slope of recurrence graph γ, parameters of RTL, ΔS and Z-function methods, and clustering of earthquakes. Estimations of seismicity are obtained for a region bordered by latitude 50.5–56.5N, longitude 156E–167E, with depths to 300 km. Earthquakes of energy classes not less than 8.5 as per the Fedotov’s classification are considered. The total seismic energy released in 2008 is estimated. According to a function of annual seismic energy distribution, an amount of seismic energy released in 2008 was close to the median level (Fig. 1). Over 2/3 of the total amount of seismic energy released in 2008 resulted from three largest earthquakes (МW ≥ 5.9). About 5 percent of the total number of seismic events are comprised of grouped earthquakes, i.e. aftershocks and swarms. A schematic map of the largest earthquakes (МW ≥ 5.9) and grouped seismic events which occurred in 2008 is given in Fig. 2; their parameters are listed in Table 1. Grouped earthquakes are excluded from the catalogue. A map showing epicenters of independent earthquakes is given in Fig. 3. The slope of recurrence graph γ and seismic activity A10 is based on the Gutenberg-Richter law stating the fundamental property of seismic process. The recurrence graph slope is calculated from continuous exponential distribution of earthquakes by energy classes. Using γ is conditioned by observations that in some cases the slope of the recurrence graph decreases prior to a large earthquake. Activity A10 is calculated from the number of earthquakes N and recurrence graph slope γ. Average slopes of recurrence graph γ and seismic activity A10 for the area under study in 2008 are calculated; our estimations give evidence that the year of 2008 was not anomalous in terms of seismicity. Based on 2D distribution of recurrence graph slope γ, it is possible to locate an area of lower values of γ in the southern part of the Kamchatka seismic zone (Fig. 4). Data on maps of normalized variation of γ for 2007–2008 and 2006–2008 (Fig. 5) confirm statistical importance of γ reduction through the last three years in the given area. Maps of 2D distribution of seismic activity A10 are constructed for 2008 and the perdiod from 1962 to 2008; values of seismic activity A10 that are normalized to the average annual seismic activity are also mapped (Fig. 6). In 2008, increased values of A10 were observed at the southern part of the Avachinsky gulf and at the northern part of the Kamchatka gulf, as well as in the northern water area of Bering Island. The anomalous behavior of parameters RTL, ΔS and clustering of earthquakes may have predictive character [Sobolev, 2000]. Negative values of RTL-parameter correspond to seismic quiescence; increasing areas of seismic ruptures ΔS correspond to foreshock activation; clustering of earthquakes can evidence that activation tends to accumulate at a future main rupture location. For 2008, three zones of seismic quiescence were defined by data (Fig. 7). For estimation points with maximum modular values of RTL (marked by the Roman numerals in Fig. 7), RTL time curves are constructed for each of the above mentioned zones (Fig. 8); they provide for defining durations of anomalies and degrees of manifestation. A map of variations of seismic rupture areas ΔS (Fig. 9) shows that seismic activity of 2008 was mainly manifested at the southern part of the Kamchatka seismic zone. In 2008, most of the earthquake clusters varying in energy also occurred in the southern part of Kamchatka (Fig. 10). The northern chain of clusters is located at the border of the developing seismic anomaly, as defined by RTL parameter. Similar to RTL technique, an objective of the Zfunction method is to reveal seismic quiescence periods as temporary anomalies of seismic process in specific areas [Wyss, Habermann, 1988] The Z-function method reveals a zone wherein seismic rates decreased by a factor of 8 during 2008 (see a dashed-line contour in Fig. 11); the given zone is partially coincident with the southern anomaly defined by RTL parameter. The curve showing time dependence Z(t) through 12 months confirms statistical significance of seismic quiescence in the given area (Fig. 12). It should be noted that epicenters of the three largest earthquakes of 2008 occurred at the areas of seismic quiescence that are revealed by both methods (see Fig. 7 and 11). Earthquake timing is shown by arrows on corresponding time curves (see Fig. 8 and 12). Taking into account that a number of indicators, which can potentially have predictive character, are well correlated in space and time, there are grounds to conclude that seismic danger is increased in the southern part of the Kamchatka seismic zone and the Kamchatka Gulf region.